Clinical Features and Outcomes of Bloodstream Infections Caused by New Delhi Metallo-β-Lactamase–Producing Enterobacterales During a Regional Outbreak. (21st January 2020) - Falcone, Marco; Tiseo, Giusy; Antonelli, Alberto; Giordano, Cesira; Di Pilato, Vincenzo; Bertolucci, Pietro; Parisio, Eva Maria; Leonildi, Alessandro; Aiezza, Noemi; Baccani, Ilaria; Tagliaferri, Enrico; Righi, Lorenzo; et al.
Abstract: Limited data about New Delhi metallo-β-lactamase (NDM) bacteremia are available. Blood isolates from 40 patients with NDM bacteremia were studied for antibiotic susceptibility and whole-genomic sequencing. NDM bacteremia has high 30-day mortality. In most cases, aztreonam-avibactam is active in vitro. Ceftazidime-avibactam plus aztreonam may represent a feasible therapeutic option.